Differentiating factors of mental adaptation to disease in women treated for gynaecological cancer - Kupcewicz, Ewa; Olewińska, Joanna; Pikus, Hanna; Jóżwik, Marcin (Journal of Education, Health and Sport, 2017)
Introduction. Cancerous disease has specific dynamics and requires the patient to be able to cope in a constantly changing situation. Aim of the study. Differentiation analysis of the influence of selected sociodemographic and medical variables on the degree of mental adaptation to disease in the group of women treated for gynecological cancer. Material and methods. The study covered 102 women after hysterectomy due to gynaecologic cancer. Mean age of patients was 56.1 (SD=10.75) years. Data was collected using the Mini-MAC Mental Adaptation to Cancer Scale and the questionnaire of own design. The p level of <0.05 was considered significant. Results. Significant differences were observed between the age of the respondents and the anxiety absorption strategy (H=10.19; p<0.02) and the fighting spirit strategy (H=10.95; p<0.02). The extent of hysterectomy significantly differentiated (H=8.10; p<0.04) the intensification of the strategy of impotence, confusion and passive disease. Larger differences in ways to deal with the disease have been revealed by women who, in addition to hysterectomy, have also been treated for other comorbidities. The differentiation was related to the strategy: fighting spirit (H=14.33; p<0.0008), helplessness/hopelessness (H=16.54; p <0.0003) and positive revalidation (H=10.98; p<0.004). Conclusions. Surveyed women showed a more constructive style of coping with cancer and more frequently used a strategy of fighting spirit and positive revalidation. Familiarity of factors differentiating the level of mental adaptation to cancer can influence the modification of the behavior of patients and be useful in the work of the therapeutic team.